Effects of proinflammatory cytokines and programmed cell death on cognitive domains in older age patients with bipolar disorder - Pei-Ying Lee; Chih Chiang Chiu; Po-Hsiu Kuo; Cho-Yin Huang; Shang-Ying Tsai; Chian-Jue Kuo; Wen-Yin Chen (Annals of General Psychiatry)
Abstract Objectives Proinflammatory cytokines are linked to cognitive deficits in bipolar disorder (BD). The programmed cell death (PD) pathway, involved in immune regulation, may impact mood disorders and dementia. Older age BD (OABD) patients face a heightened risk of cognitive decline, yet studies exploring the underlying mechanisms in this population are scarce. Aim of this study is to investigate proinflammatory cytokines and the PD pathway in OABD, for their correlation with clinical features and neuroaxonal integrity, and the impact on cognitive domains. Methods Eighty-seven euthymic OABD patients were assessed using the Brief Assessment of Cognition in Affective Disorders. We measured CRP, IL-6, TNF-α, TNF-R1, TNF-R2, PD-1, and PD-L1. Neurofilament light chain (NfL) was used to gauge neuroaxonal integrity. Associations between cytokines, PD-1/PD-L1, and cognition were examined using linear regression models. Results The average age of the OABD patients was 59.64 with a mean illness duration of 27.19 years. NfL levels positively correlated with TNF-R2 levels. Regression analysis revealed a negative association between TNF-R1 and motor speed and verbal fluency, while TNF-R2 showed positive associations with these cognitive domains. PD-1 was negatively associated with composite score, especially in motor speed and working memory, while PD-L1 was positively associated with executive function. Conclusion This is the first study to simultaneously examine the proinflammatory system and the PD-1/PD-L1 pathway in a clinical OABD sample, with findings suggesting that both systems impact cognitive function in OABD patients. Further research is needed to explore the neuroinflammatory mechanisms underlying BD’s neurodegenerative course.